Testosterone Increases the Emission of Ultrasonic Vocalizations With Different Acoustic Characteristics in Mice - Kikusui, Takefumi; Sonobe, Miku; Yoshida, Yuuki; Nagasawa, Miho; Ey, Elodie; de Chaumont, Fabrice; Bourgeron, Thomas; Nomoto, Kensaku; Mogi, Kazutaka (Frontiers in Psychology, 2021)
Testosterone masculinizes male sexual behavior through an organizational and activational effects. We previously reported that the emission of ultrasonic vocalizations (USVs) in male mice was dependent on the organizational effects of testosterone; females treated with testosterone in the perinatal and peripubertal periods, but not in adults, had increased USV emissions compared to males. Recently, it was revealed that male USVs have various acoustic characteristics and these variations were related to behavioral interactions with other mice. In this regard, the detailed acoustic character changes induced by testosterone have not been fully elucidated. Here, we revealed that testosterone administered to female and male mice modulated the acoustic characteristics of USVs. There was no clear difference in acoustic characteristics between males and females. Call frequencies were higher in testosterone propionate (TP)-treated males and females compared to control males and females. When the calls were classified into nine types, there was also no distinctive difference between males and females, but TP increased the number of calls with a high frequency, and decreased the number of calls with a low frequency and short duration. The transition analysis by call type revealed that even though there was no statistically significant difference, TP-treated males and females had a similar pattern of transition to control males and females, respectively. Collectively, these results suggest that testosterone treatment can enhance the emission of USVs both in male and female, but the acoustic characteristics of TP-treated females were not the same as those of intact males.